ERGONOMIC RISKS IN SEMI-MECHANIZED CUTTING OPERATIONS IN THE SOUTHERN AMAZON - Silva, Ivan Cleiton Oliveira; Lopes, Eduardo da Silva; Minette, Luciano José; Koehler, Henrique Soares (Floresta, 2024)
Sustainable forest management in the Amazon must be carried out to guarantee the maintenance of forest resources and the safety and health of workers. In this region, workers are subject to various ergonomic risks that compromise their quality of life. In this context, the objective was to assess the ergonomic risks to which workers are exposed when cutting trees of different densities. Assessments of occupational heat exposure levels and physical workload were performed using a portable digital IBUTG thermometer and heart rate monitor, respectively. The IBUTG limits indicated the workers’ exposure to thermal overload. The tree-cutting operation did not indicate a high physical workload or potential postural risks, without the requirement for immediate action to change the work routine. Thermal overload is a factor that requires the adoption of mitigating ergonomic measures to preserve the health of workers in the Amazon region.